(3eONd GdbjeI hEJNGP GdbQGQGJs - (3eMeO UdGM(B, (3GdMfGhjs; (3LdGd GHQGgje GdYHO(B, s ((3GdEScfOQjI(B:s (3GdOGQ GdLGeYjI(B,s, 2006)
(3EWdGdI YGeI Ydi GdEOGQI GdeGdjI, GdJfHD GdeGdj, bQGQGJ GdEfaGb GdQCSeGdj aj Xd XQha GdJCcO, bQGQGJ GdEJaGb GdQCSeGdj aj Xd XQha GdNWQ, Gdgjcd GdeGdj, JcdaI GdCehGd, JCKjQ gjcd QCS GdeGd Ydi GdbjeI GdefTGI, JGKjQ GdJhRjYGJ Ydi bjeI GdefTCI, Jbjje GdCOGA GdeGdj, GdEJLGgGJ GdMOjKI aj Jbjje COGA GdefTBJs
Keywords: (3EJNGP GdbQGQs; (3GdEOGQIs; (3GdEOGQI GdeGdjIs